Financial Feasibility of Palm Sugar Business in Ogomoli Village, District Galang Tolitoli Regency - Andi Sahri Alam; Rafiuddin; Budi Setiawan; Hamzari; Pinki Kurniawan (Postgraduate, University of Mataram, 2024)
Sugar palm (Arenga pinnata) is a type of plant that has been known for a long time because almost all parts of this palm tree can be used and contribute to people's income. Sugar palm as an NTFP product has a very important role in the development of NTFPs in Indonesia can support the economy of rural communities and has a bright market and high demand. This research aims to determine the financial feasibility of the palm sugar business and determine community income from selling palm sugar in Ogomoli Village, Tolitoli Regency, Galang District. The method used in this research is the census method (which is studied in measuring variables), namely, all individuals in the population are enumerated (investigated or interviewed) as respondents. Results of research carried out in Ogomoli Village, Galang District, Tolitoli Regency. Took a sample of 44 people. Based on the research results above, the average income from the palm sugar business in Ogomoli Village, Galang District, Toli-Toli Regency obtained by respondents was equal to. Rp. 19.584.00/ year with an average NPV of Rp. 105.950.39, with a Net B/ C of Rp. 5.33. The IRR value is 11.50% and the payback period (PP) in the palm sugar business is the profit earned or returned in the sixth year.